2013
DOI: 10.1186/1745-6215-14-309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Housing First program in patients with severe mental disorders in France: study protocol for a randomized controlled trial

Abstract: BackgroundRecent studies in North American contexts have suggested that the Housing First model is a promising strategy for providing effective services to homeless people with mental illness. In the context of the highly generous French national health and social care system, which is easily accessible and does not require out-of-pocket payment, the French Health Ministry insists on rigorous techniques, including randomized protocols, to evaluate the impact of Housing First approaches in France.Method and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 59 publications
0
28
0
1
Order By: Relevance
“…The French Housing First program is a multicenter randomized controlled trial conducted in the following French cities: Lille, Marseille, Paris, and Toulouse 25 and is designed to assess the impact of a Housing First intervention on health outcomes and costs over a period of 24 months on homeless people with severe mental illness compared to Treatment- As-Usual (five evaluations: baseline, 6, 12, 18 and 24 months). Baseline (t0) was the only data used in the present analysis, before any intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The French Housing First program is a multicenter randomized controlled trial conducted in the following French cities: Lille, Marseille, Paris, and Toulouse 25 and is designed to assess the impact of a Housing First intervention on health outcomes and costs over a period of 24 months on homeless people with severe mental illness compared to Treatment- As-Usual (five evaluations: baseline, 6, 12, 18 and 24 months). Baseline (t0) was the only data used in the present analysis, before any intervention.…”
Section: Methodsmentioning
confidence: 99%
“…A growing literature supports the effectiveness of Housing First (HF) for individuals who are both homeless and mentally ill. HF promotes client choice, and has demonstrated impacts on community integration , residential stability , client satisfaction and service costs . Several nations have mounted large‐scale initiatives to address chronic homelessness using HF, including the United States , Canada , France and Australia . However, empirical evidence concerning the effectiveness of HF for people with prominent substance use problems has been described as ‘mixed and unsettled’ .…”
Section: Introductionmentioning
confidence: 99%
“…We identified 43 randomized controlled studies (RCTs) reported in 78 publications (24,26,27,39,40, that met our inclusion criteria, and two studies in progress (31,82). See Appendix 9 for a description of the studies in progress.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Appendix 9: Description of studies in progress (82) This is a randomized trial aiming to assess the effect of Housing First on health outcomes and costs for adults who are homeless are at risk of becoming homless and have either schizophrenia, bipolar disorder or a severe disability. Housing stability is a secondary outcome.…”
Section: Information About This Reviewmentioning
confidence: 99%